2003
DOI: 10.1002/pssc.200303843
|View full text |Cite
|
Sign up to set email alerts
|

Model for the strain‐induced reflectance‐difference spectra of InGaAs/GaAs (001) epitaxial layers

Abstract: We present a model to describe the Reflectance-difference (RD) spectra of InGaAs grown on GaAs (001) at T=500 o C, in the energy range from 2.3-3.5 eV. The model assumes the presence of an orthorhombic strain in the InGaAs epilayer that accounts for an anisotropic process of nucleation of InGaAs islands. We show that the developed model leads to accurate fits to the experimental RD spectra of InGaAs/GaAs for epilayer thickness both below and above of the critical thickness for the 2D-3D growth-mode transition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…We may thus conclude that the RD signal in the 3D growth comprise a substantial component originated in InGaAs islands that grow anisotropic. In agreement with this conclusion, elsewhere we have shown that the RD line shape of 3D In 0.3 Ga 0.7 As/GaAs (001) films in the energy range from 2.4-3.1 eV can be accurately modeled assuming that the InGaAs islands on the epilayer are under an orthorhombic strain [9,10]. This strain may be originated by the well-known anisotropy in the diffusion coefficients of the atomic species on the growth surface that may lead to InGaAs islands with anisotropic shapes [16] and thus with an anisotropic elastic strain relaxation.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We may thus conclude that the RD signal in the 3D growth comprise a substantial component originated in InGaAs islands that grow anisotropic. In agreement with this conclusion, elsewhere we have shown that the RD line shape of 3D In 0.3 Ga 0.7 As/GaAs (001) films in the energy range from 2.4-3.1 eV can be accurately modeled assuming that the InGaAs islands on the epilayer are under an orthorhombic strain [9,10]. This strain may be originated by the well-known anisotropy in the diffusion coefficients of the atomic species on the growth surface that may lead to InGaAs islands with anisotropic shapes [16] and thus with an anisotropic elastic strain relaxation.…”
Section: Resultssupporting
confidence: 74%
“…Elsewhere, we reported on in situ RD measurements in In x Ga 1-x As grown by MBE that show a sharp increase in RD amplitude at 2.5 eV at the onset of the 2D-3D growth transition [9,10]. This, as a result of the formation of anisotropic 3D islands.…”
Section: Introductionmentioning
confidence: 94%
“…The insight that RAS has provided into the complexities of the GaAs(001) surface has naturally led to its use in the characterization of the early stages of the growth of semiconducting structures on GaAs(001). These range from the Si/GaAs(001) [50] and Ge/GaAs(001) systems [206][207][208], the latter prompted by the good lattice match between the materials, to systems where the lattice mismatch leads to the formation of quantum dots such as In/GaAs(001) [209][210][211][212]. RAS is also well suited to the study of the formation of metal-semiconductor contacts as illustrated by the studies of the interfaces between alkali metals and GaAs(001) [213,214] and of Cs deposited on a range of III-V (110) cleaved surfaces [215].…”
Section: Gaas(001)mentioning
confidence: 99%
“…Such islands are fully strained at the base but partially relaxed at the top. Further, since it is known that such islands are anisotropic in shape [12,13], the strain at the top is also anisotropic. The same explanation can be adopted for RA oscillations during homoepitaxial growth.…”
Section: Resultsmentioning
confidence: 98%